2023
DOI: 10.5455/ovj.2023.v13.i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efflux pump inhibitory activity of some plant extracts and using them as adjuvants to potentiate the inhibitory activity of some antibiotics against Staphylococcus aureus

Abstract: Background: Antibiotic resistant pathogens became a real global threat for human and animal health. This needs to concentrate the efforts to minimise and control these organisms. Efflux pumps are considered as one of the important strategies used by bacteria to exclude the harm materials out of the cell. Inhibition of these pumps can be an active strategy against multidrug resistance (MDR) pathogens. There are two source of efflux pump inhibitors can be used, chemical and natural inhibitors. The chemical origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Maximum the gram-positive bacteria was inhibited by B.monnieri extracts at lower concentration 49 . The present investigation revealed that gram-negative and gram-positive bacteria were inhibited with a minimum concentration of B. monnieri aqueous and methanol extracts.The propolis, rosemary, clove, capsaicin, and cumin extracts showed the minimum inhibition concentration against the S. aureus 56 . However, the present investigation revealed that the B. monnieri 7.81µg/ml concentration showed extraordinary inhibition against S. aureus.The microtiter plate technique was used to assess biofilm formation.…”
Section: Discussionmentioning
confidence: 96%
“…Maximum the gram-positive bacteria was inhibited by B.monnieri extracts at lower concentration 49 . The present investigation revealed that gram-negative and gram-positive bacteria were inhibited with a minimum concentration of B. monnieri aqueous and methanol extracts.The propolis, rosemary, clove, capsaicin, and cumin extracts showed the minimum inhibition concentration against the S. aureus 56 . However, the present investigation revealed that the B. monnieri 7.81µg/ml concentration showed extraordinary inhibition against S. aureus.The microtiter plate technique was used to assess biofilm formation.…”
Section: Discussionmentioning
confidence: 96%